Emotional Eating among Final Year Undergraduate Female Students of Faculty of Public Health Universitas Indonesia During COVID-19 Pandemic in 2021 - Adinda Safira Salsabiela; Wahyu Kurnia Yusrin Putra (Indonesian Journal of Public Health Nutrition, 2022)
Emotional eating is defined as the tendency to excessively consuming food which often high in sugar, salt, and fat levels in response to negative emotions. Uncontrolled emotional eating will increase the risk of eating disorders such as bulimia nervosa and binge-eating disorder, obesity, cardiovascular diseases, and type II diabetes. This study aims to find out about the relationship between perceived stress, anxiety, academic stressors, social media engagement, COVID-19 infection history in respondent and their family members, and mindfulness with emotional eating among 106 final year undergraduate female students of the Faculty of Public Health Universitas Indonesia during the COVID-19 pandemic in 2021. This cross-sectional quantitative study shows that there are about 20,8% of respondents who has an emotional eating tendency. There are significant differences between social media engagement and observing facet (p-value < 0,05) with emotional eating. Young adults should discover more about their triggers and positive coping strategies, to use social media wisely, and to eat mindfully.